New Records of Stoneflies (Insecta: Plecoptera) in National Park Shar Mountain (R. North Macedonia) - Rušiti-Dauti, Ajten; Slavevska-Stamenković, Valentina; Sivec, Ignac; Ibrahimi, Halil; Iseni, Gazmend; Bilalli, Astrit; Cvetkovska-Gjorgjievska, Aleksandra; Hinić-Jordanovska, Jelena (Institute for Biodiversity and Ecology, 2024)
The collection of stoneflies in Shar Mountain resulted with records of four species (Isoperla bosnica Aubert, 1964, Isoperla albanica Aubert, 1964, Nemoura uncinata Despax, 1934, Nemoura asceta Murányi, 2007) for this mountain massif. From the mentioned species Nemoura asceta Murányi, 2007 and Isoperla bosnica Aubert, 1964 are endemic species to the Balkan Peninsula, while Nemoura asceta Murányi, 2007 is recorded for the first time in the country. These results highlight the importance of Shar Mountain as a stoneflies biodiversity hotspot, increasing the focus on the conservation status of these rare species.
Keywords: Stoneflies, new records, endemic species, Shar Mountain, R. North Macedonia